2006
DOI: 10.17221/3904-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Pig carcass quality in relation to carcass lean meat proportion

Abstract: ABSTRACT:The objective of the study was to quantify differences in the carcass composition of pig carcasses with different lean meat proportions. Totally 132 carcasses with lean meat proportions ranging from 45 to 65% were analysed. The average lean meat proportion in the analysed set of carcasses was 55.38% (s = 4.319). The carcasses were classified into the groups according to their lean meat proportion (R, 45.0 to 49.9%; U, 50.0 to 54.9%; E, 55.0 to 59.9%; S, more than 60.0%). Carcasses from each group were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 3 publications
5
9
0
Order By: Relevance
“…The calculated percentage of lean meat in our study is widely in agreement with Pulkrabek et al (2006). However, Wiegand et al (2002) have found that dietary CLA did improve pig composition as measured by loin muscle area.…”
Section: Discussionsupporting
confidence: 88%
“…The calculated percentage of lean meat in our study is widely in agreement with Pulkrabek et al (2006). However, Wiegand et al (2002) have found that dietary CLA did improve pig composition as measured by loin muscle area.…”
Section: Discussionsupporting
confidence: 88%
“…Over the last few years an increase in slaughter mass and average lean meat content of the carcass has been achieved (Lisiak et al, 2012). In agreement with the observations of other authors, we reported that the higher meat classes and lower average backfat thickness are associated with a decrease in the percentage of belly in the carcass (Stupka et al, 2004;Pulkrábek et al, 2006;Duziński et al, 2015), but with an increasing muscle mass and percentage of meat in belly (Lonergan et al, 2001). A belly muscle content >50% is considered a preferred feature in terms of production and consumption (Pulkrábek et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…Although no significant differences (P>0.05) were determined in terms of meat contents in carcasses, pigs of higher body mass had a very significantly (P<0.01) bigger relative share of abdominal-rib part meat in carcasses, as well as a smaller relative share of ham meat in carcasses, but this was not statistically significant (P>0.05). Pulkrabek et al (2006). In researches of crossbreds of Great Yorkshire, Swedish Landrace and Pietren fattened to 90.30 kg, 100.40 kg, 110.130 kg 120.50 kg and 130.20 kg body mass, Senčić et al (2005) determined that as final body mass of fattened pigs was increasing, a relative share of ham meat in carcasses was decreasing to a statistically significant extent , as well as a relative share of back and shoulder meat, but not statistically significant (P>0.05).…”
Section: Resultsmentioning
confidence: 99%